Development of Electrically Conductive Cellulose Nanofiber FilmComposited with Carbon Nanotubes Using a Spray Method. Issue 1 (November 2020) - Tominaga, M; Kuwahara, K; Tsushida, M; Shida, K
Abstract: Nanocellulose is made from wood, cotton, cellulose-rich materials, and organisms by mechanical methods or chemical dissolution. Nanocellulosefilms are a flexible substrate with excellent thermal and chemical stability. These excellent properties are useful as electrodes for wearable type devices that replace plastic films. In addition, cellulose is both biodegradable and eco-friendly. Problem is that the cellulose film does not have electrical conductivity. In this study, a nanocelluloseconductive film made of composite carbon nanotubes was produced by a simple spray method. It was investigated whether this conductive film is useful as an electrode for electrochemical measurement.